(untitled) (Historia, 2021)
Christi van der Westhuizen begins her book, Sitting Pretty: White Afrikaans Women in Postapartheid South Africa, with the then president, Nelson Mandela’s invitation to Afrikaner women to join the ranks of "a newly imagined, inclusive community" (p 3), during the opening of the first democratic parliament on 24 May 1994. Through his reference to Ingrid Jonker, who recognised the volk’s black other in her poem "The Child Who Was Shot Dead by Soldiers at Nyanga", Mandela pointed out the democratic potential opened for Afrikaner women’s subjectivities in South Africa’s fledgeling democracy. Van der Westhuizen investigates how Afrikaans women responded to Mandela’s offer of identification and if they stepped into the subject positions of democratic discourse in terms of race, class, gender and sexuality. She asks if Jonker’s counterparts readily absorbed postapartheid discourses of the humanisation of the volk’s others and how they, in turn, produced these discourses.